PERILAKU ORGANIZATIONAL CITIZENSHIP BEHAVIOR BERDASARKAN KARAKTERISTIK PEGAWAI DI RUMAH SAKIT - Ria Chandra Kartika; M. Risya Rizki (UNUSA Press, 2019)
Human resources are an important aspect of organizational success. In the last three years, outpatient visits at RSIA NUN Surabaya decreased by 5.32%. The results of the identification showed that, one of the causes of the decrease in visits was patient dissatisfaction with the service of the officers. The objectives of this research were analyzing Organizational Citizenship Behavior (OCB) based on characteristics of employees in the hospital. This research is analytic descriptive with cross sectional study design. The samples were 34 employees were selected using purposive sampling. Result of this research showed that employees who had organizational citizenship behavior in the fewer categories were employees who had more than 32 years of age (≥ 32 years) with 77.8% presentations. Employees who have Organizational Citizenship Behavior (OCB) with fewer categories are employees who have a work period of less than 2 years with 100% presentation. The conclusion of this study is that employees who are more mature tend to have low OCB. Employees who have a low working period tend to have a low OCB. Therefore, it is important for hospital management to improve relationships between employees through gathering and maximizing employee potential when undergoing training for new employees.